Melioidotic septic arthritis: a case report and literature review. - Raja, N.S. (Elsevier, 2007)
Burkholderia pseudomallei, the causative agent of melioidosis, is endemic in southeast Asia and northern Australia. In recent years, the incidence of melioidosis has increased worldwide. Septic arthritis is a rare but well-recognized manifestation of melioidosis. Patients with underlying medical conditions, such as diabetes mellitus, renal impairment, cirrhosis, and malignancy are at greater risk. The presentations of melioidotic septic arthritis often mimic other disease processes and patients may not always be clinically septic. We present a case of septic arthritis due to B. pseudomallei in a 66-year-old male with diabetes mellitus presenting with a history of fever and ankle swelling. Follow-up ankle X-ray showed soft tissue swelling. Synovial fluid and blood samples grew B. pseudomallei. The patient improved gradually after parenteral administration of ceftazidime (2 g 8-hourly) and cotrimoxazole (1440 mg 8-hourly). He was discharged on oral cotrimoxazole (1440 mg 12-hourly), doxycycline (100 mg 12-hourly), and chloramphenicol (500 mg 6-hourly) for 6 months. This case highlights the possible occurrence of melioidotic septic arthritis, and the importance of prompt initiation of appropriate antimicrobials to achieve good outcomes.